Neoconopodium paddarensis, a new species of Apiaceae from Jammu and Kashmir, Western Himalaya, India - Thakur, Sajan; Singh, Bikarma; Tashi, Nawang; Dutt, Harish Chander (Phytotaxa, 2020)
Neoconopodium paddarensis, belonging to the family Apiaceae from the Paddar valley, Himalayan Jammu & Kashmir, India is described here as a new species. It shows restricted distributional range and so far, is only known from the Atholi mountain, Paddar valley, within the Himalayan centre of endemism. It is a pinkish white flowered species, and unusual in being a small herb with tripinnate leaves. Other diagnostic features include pubescent stem and leaf base, root hairs, leaflet size and structure, defined carpel and fruit size. The species shows certain similarities with N. capnoides, but differs in both vegetative and reproductive characters.